An Overview of Aspects of the An Gúm Catalogue - Ó hUallacháin, Breandán (Studia Celtica Posnaniensia, 2026)
An Gúm, or ‘The Scheme’ as it translates into English, also known as An Scéim Foillsiúcháin [The Publication Scheme], was created in the early years of the Irish Free State to provide Irish language reading material. The aim of this paper is to focus on a vital and complex aspect of Irish language revival at the beginning of the fledgling Irish Free State, as An Gúm remains an unknown entity to many. It was stated in a review in Irish Books (no date) of the Irish translation of Robert Emmet that reading matter for the large and increasing number of Irish language speakers was required for the advancement of Gaeilge outside the Gaeltacht. It mentioned that the best Irish language literature is that which comes from the Irish-speaking areas, but while a library of Irish-language materials was being created well-chosen translations would suffice (Ó hUallacháin 2021 A6 [98]). Many of the early An Gúm publications were translations of famous English-language books such as Dracula. There were translations of other European authors, as well as translations of books written in English by Irish authors. An Gúm published musical scores during this period – some of them specifically for educational purposes in schools. This paper will discuss the recommending and commissioning of works, procurement of a printing and publishing company, hiring of a designer for the book cover, copyright issues, choosing, monitoring and paying of translators, as well as internal and external examination of material.